2001
DOI: 10.1038/ng1001-189
|View full text |Cite
|
Sign up to set email alerts
|

The gene mutated in ataxia-ocular apraxia 1 encodes the new HIT/Zn-finger protein aprataxin

Abstract: The newly recognized ataxia-ocular apraxia 1 (AOA1; MIM 208920) is the most frequent cause of autosomal recessive ataxia in Japan and is second only to Friedreich ataxia in Portugal. It shares several neurological features with ataxia-telangiectasia, including early onset ataxia, oculomotor apraxia and cerebellar atrophy, but does not share its extraneurological features (immune deficiency, chromosomal instability and hypersensitivity to X-rays). AOA1 is also characterized by axonal motor neuropathy and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
311
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(325 citation statements)
references
References 21 publications
4
311
1
9
Order By: Relevance
“…Instead, removal of this 5'blocking lesion is most likely the result of strand displacement and Fen1-mediated hydrolysis and would be shuttled into the long-patch complex depicted in Fig 2, bottom right complex. In 2001, the gene responsible for ataxia-ocular apraxia 1 (AOA1), a neurological disorder similar to ataxia-telangiectasia, was identified. The protein was named aprataxin (APTX) and is found to share a distant homology with PNKP [84]. Interestingly, APTX also interacts in vitro and in vivo with XRCC1 [72][73][74][75][76] and co-immunoprecipitated with PARP1 [73,74].…”
Section: Gap Tailoringmentioning
confidence: 99%
“…Instead, removal of this 5'blocking lesion is most likely the result of strand displacement and Fen1-mediated hydrolysis and would be shuttled into the long-patch complex depicted in Fig 2, bottom right complex. In 2001, the gene responsible for ataxia-ocular apraxia 1 (AOA1), a neurological disorder similar to ataxia-telangiectasia, was identified. The protein was named aprataxin (APTX) and is found to share a distant homology with PNKP [84]. Interestingly, APTX also interacts in vitro and in vivo with XRCC1 [72][73][74][75][76] and co-immunoprecipitated with PARP1 [73,74].…”
Section: Gap Tailoringmentioning
confidence: 99%
“…Despite literature that is sparse outside of Portugal (27) and Japan (28), AOA has been found in many ethnic groups and does not appear to be a Portuguese or Japanese disease but rather a disease that is rare but ubiquitous (26). Two groups succeeded in positional cloning of an AOA disease locus to the APTX gene encoding Aprataxin on 9p13 (29,30).…”
Section: Aprataxin: a Zn-finger-containing Hint Family Member That Ismentioning
confidence: 99%
“…Human Aprataxin is expressed in two splice forms (30). The minor splice form encodes a predicted polypeptide of 168 amino acids consisting of a Hint domain and an apparent C(2)H (2) zinc finger C-terminal to the Hint domain (29,30).…”
Section: Aprataxin: a Zn-finger-containing Hint Family Member That Ismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, seizures in the affected sister disappeared on CoQ 10 therapy and her anti-convulsant medication was discontinued (Musumeci et al, 2001). In these 3 patients, we demonstrated that CoQ 10 deficiency was secondary to a stop codon mutation in the APTX gene, which is known to cause ataxia-oculomotor-aprataxia 1 (AOA1) (Quinzii et al, 2005,Date et al, 2001Moreira et al, 2001). Results from measuring CoQ 10 concentration in skeletal muscle from 12 additional patients from 6 different families with AOA1 confirmed this data (data not published).…”
mentioning
confidence: 94%